Um passeio pelos bosques ficcionais de Antonio Tabucchi - Andrade, Cátia Inês Negrão Berlini de [UNESP] (My University, 2012)
The Italian writer Antonio Tabucchi (Pisa-1943, Lisbon-2012) is considered by the critic as one of the most representative voices in the contemporary European literature. The Literature, according to Tabucchi, exerts a fundamental role in society and it, still according to the writer, must cause disquietude, evoke doubts, raise questions and not tranquilize people’s mind. Thereby, it’s noticed that it’s one of the reasons why the tabucchian narrative incessantly dialogues with Luigi Pirandello’s and Fernando Pessoa's poetics, establishing a great fictional game in wich the people, the truths, the history and the world are shown, at the least, duplicated.

O escritor italiano Antonio Tabucchi (Pisa-1943, Lisboa-2012), é considerado pela crítica como uma das vozes mais representativas da literatura europeia contemporânea. A literatura, segundo Tabucchi, exerce um papel fundamental na sociedade e ela, ainda de acordo com o escritor, deve causar inquietude, suscitar dúvidas, colocar questões e não tranquilizar a mente das pessoas. Precebemos, desse modo, que essa é uma das razões que faz com que a narrativa tabucchiana dialogue incessantemente com as poéticas de Luigi Pirandello e Fernando Pessoa, instaurando um grande jogo ficcional em que as pessoas, as verdades, a história e o mundo aparecem, no mínimo, duplicados.
Keywords: Antonio Tabucchi; Italian contemporary narrative; Literature and society; Fernando Pessoa; Luigi Pirandello; Antonio Tabucchi; Narrativa italiana contemporânea; Literatura e sociedade; Fernando Pessoa; Luigi Pirandello